Introduction to urban agriculture : Uvod u gradsku poljoprivredu - Brezinščak, Luka (Array, 2021)
An increasing number of population in the cities has problems with food security, transportation and environmental protection. To misticate these problems, a new type of agriculture has been established: Urban Agriculture (UA). In this paper, we are introducing the concept of UA and provide basic information on the definition and forms of UA. The article aims to provide insight into the general concept of UA for sustainable city development. UA has a positive influence on social, environmental and economic life in the cities, which should encourage members of the government and private sector to utilize UA as an important part in city planning. However, there are reservations which should be taken into account, but by raising awareness we add to a better understanding of mechanisms in UA.